Fatores de risco para acinetobacter baumannii em isolados de pacientes em uma unidade de terapia intensiva de um hospital público do Paraná - Silva, Mirian Carla Bortolamedi da (2022)
Acinetobacter baumannii (A. baumannii) is an opportunistic pathogen that has caused outbreaks of global infections and an increasing profile of antimicrobial resistance. Objective: To identify risk factors for A. baumannii infection in isolated patients hospitalized in an Intensive Care Unit (ICU) of a tertiary public hospital in Paraná, Brazil. Material and Methods: A retrospective paired case-control study (ratio 1: 2) was conducted from January 2018 to December 2020. Patients in the case group admitted to the ICU with A. baumanni (n=68 cases) were compared with patients in the control group without Infection by A. baumannii (n=136) matched by age (±10years), sex, ICU stay (±5 days). Conditional multiple logistic regression was used to determine statistically significant risk factors based on the results of bivariate analyses. Results: Mortality was higher in infected (cases) than in non-infected patients (51.5% vs. 39.7%). The incidence and bacterial resistance increased annually. At bivariate analysis, cases had longer hospital stays (median 35 vs. 22 p<0.001) and longer remained in the ICU (median 23 vs. 16, p<0.001). A long time of use of a central venous catheter (median 25 vs. 18, p>0.001), the vesical catheter (median 29 vs. 20, p<0.001), and mechanical ventilation (median 17 vs. 12, p<0.001). Cases also presented a higher frequency of admission by transfer from another unit (p<0.001) previous hospitalization (p=0.011), colonization (p<0.001), surgical procedure (p=0.013), and use of an enteral tube (p=0.011) than controls. The multivariate analysis showed that hospitalization time (OR=1.06; CI95%:(1.03-1.08), transfer from another unit (OR=5.03; CI95% 2.30-10.98) and colonization (OR= 9.32; CI95% 3.52-24.72) were independently associated with infection. Conclusions: We showed an increase in Infections by A. baumannii and antimicrobial resistance, need for surveillance, and constant evaluation of control actions. Risk factors were colonization, previous hospitalization, and hospitalization time. Knowing them is essential for the decision-making of professionals and optimization of prevention, control, and therapeutic management actions.